2018
DOI: 10.1097/inf.0000000000002040
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Pediatric Drug-resistant Tuberculosis in Mumbai, India, and Its Outcome

Abstract: DR-TB is increasing in Mumbai, India. Based on the DST results, individualised therapy would be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The ability of Xpert® MTB/RIF and phenotypic detection of TB drug resistance cannot be underscored as it can pave a way to complementary and confirmatory WGS in early detection of resistance. Studies have shown phenotypic susceptibility tests to serve as reference standards [25], and that both Xpert assay and DST can provide information on polyresistance in pre-XDR-TB [26] despite varying sensitivities [27,28]. The current practice in diagnosing drug resistant tuberculosis is through the WHO-approved probe-based assays like Xpert® MTB/RIF (Cepheid, USA) for RIF [16] and either genotype MTBDRplus for RIF and INH or genotype MTBDRsl (Hain Lifesciences, Germany) for aminoglycosides/capreomycin and fluoroquinolones that must be confirmed with culture-based DST [29].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Xpert® MTB/RIF and phenotypic detection of TB drug resistance cannot be underscored as it can pave a way to complementary and confirmatory WGS in early detection of resistance. Studies have shown phenotypic susceptibility tests to serve as reference standards [25], and that both Xpert assay and DST can provide information on polyresistance in pre-XDR-TB [26] despite varying sensitivities [27,28]. The current practice in diagnosing drug resistant tuberculosis is through the WHO-approved probe-based assays like Xpert® MTB/RIF (Cepheid, USA) for RIF [16] and either genotype MTBDRplus for RIF and INH or genotype MTBDRsl (Hain Lifesciences, Germany) for aminoglycosides/capreomycin and fluoroquinolones that must be confirmed with culture-based DST [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mumbai contributes 22% of TB cases reported in the state of Maharashtra [ 15 ]. The city is known as a TB and DR-TB hotspot of the country and has a high proportion of MDR-TB with fluoroquinolone resistance and advanced TB resistance profiles [ 16 18 ]. M-East Ward is one of the wards in Mumbai which has lowest development index and majority of the residents live in slums [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of LTFU among childhood TB patients ranges from 4 to 37% [52][53][54][55][56][57]. Among the children with drug-resistant TB, it ranges from 5 to 19.09% [58][59][60]. These figures are much similar to those of the adult population.…”
Section: Proportion Of Ltfumentioning
confidence: 98%